What is the problem? The obstacles to the electrification of urban mobility in Mediterranean cities. Case study of Valencia, Spain. (September 2022) - Bastida-Molina, Paula; Ribó-Pérez, David; Gómez-Navarro, Tomás; Hurtado-Pérez, Elías
Abstract: The transport sector is answerable for around a quarter of the global CO2 emissions sent into the atmosphere, and 50% of the greenhouse gases in the cities. Considering a staggered introduction of renewable sources in the electricity mix, the introduction of electric vehicles (EVs) in the urban transport network arises as a necessary environmental solution. However, their integration is facing a wide range of barriers, many of them only qualitatively known, or uncertain. This paper presents a multicriteria methodology to assess such obstacles to the electrification of urban transport of Mediterranean flat medium cities. This analysis considers context analysis, literature review, and the application of the Multi Criteria Decision Making Method: Analytic Network Process, with the aid of a panel of experts representing quadruple helix involvement (Government, Business, Society and Academia). As a case study, the city of Valencia (Spain) was chosen, which has been in a deep transition of mobility in recent decades. Results revealed that the most influential barriers turned out to be the insufficient subsidies for EVs' development, the battery autonomy power and the CapEx of batteries. Moreover, private passenger transport followed by freight transport ranked as the most affected urban transport alternatives. Highlights: Multicriteria method to assess the obstacles to the introduction of EVs in Mediterranen cities. The methodology includes context analysis, literature review and ANP application. Insufficient subsidies results the main barrier for EVs' development. Private passenger transport is the most affected urban transport alternative.